2014
DOI: 10.1016/j.atmosenv.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A new hybrid spatio-temporal model for estimating daily multi-year PM2.5 concentrations across northeastern USA using high resolution aerosol optical depth data

Abstract: Background The use of satellite-based aerosol optical depth (AOD) to estimate fine particulate matter (PM2.5) for epidemiology studies has increased substantially over the past few years. These recent studies often report moderate predictive power, which can generate downward bias in effect estimates. In addition, AOD measurements have only moderate spatial resolution, and have substantial missing data. Methods We make use of recent advances in MODIS satellite data processing algorithms (Multi-Angle Implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
248
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 278 publications
(254 citation statements)
references
References 39 publications
4
248
0
2
Order By: Relevance
“…Missing observations on the 1-km × 1-km grid for the period of October 2003-December 2011 were also replaced with measurements from the 10-km × 10-km grid. Out-of-sample cross-validation showed a good fit of the 10-km × 10-km model (R 2 = 0.81) and an excellent fit of the 1-km × 1-km model (R 2 = 0.87) (18,19).…”
Section: Spatiotemporally Resolved Modeling Of Particulate Matter Levelmentioning
confidence: 96%
See 2 more Smart Citations
“…Missing observations on the 1-km × 1-km grid for the period of October 2003-December 2011 were also replaced with measurements from the 10-km × 10-km grid. Out-of-sample cross-validation showed a good fit of the 10-km × 10-km model (R 2 = 0.81) and an excellent fit of the 1-km × 1-km model (R 2 = 0.87) (18,19).…”
Section: Spatiotemporally Resolved Modeling Of Particulate Matter Levelmentioning
confidence: 96%
“…We used the average PM 2.5 level during the year prior to each visit at each participant's residential address to assess the longterm association of air pollution with metabolic dysfunction. The model incorporates fine-scale local land-use regression analysis and satellite-measured aerosol optical depth (18 (18,19). Missing observations on the 1-km × 1-km grid for the period of October 2003-December 2011 were also replaced with measurements from the 10-km × 10-km grid.…”
Section: Spatiotemporally Resolved Modeling Of Particulate Matter Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sparse measurements in winter as well as other additional factors such as rainfall tend to limit the model prediction. In future research, we will attempt to incorporate other influential predictors into a mixed-effects model [62], which could generate daily PM 2.5 predictions to minimize the bias.…”
Section: Resultsmentioning
confidence: 99%
“…Also, some studies found that the correlation between AOT and PM concentration is impacted by meteorological conditions [13][14][15][16][17][18][19], boundary layer height [20][21][22], land use [23] and geographical location, [24] etc. Recently, researchers developed approaches using various statistical methods, from linear regression models [25,26] to more complex multiple regression and neural network techniques [13,27], generalized additive mixed models (GAMs) [23,28], and mixed effects models [29,30].…”
Section: Introductionmentioning
confidence: 99%